Brottsprevention i straffvälfärdspolitikens tid – Samverkanstankens historiska rötter - Paula Wahlgren (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Cooperation between authorities is a central part of present-day crime prevention in Sweden. At the same time, the idea of cooperation has an extensive heritage within Swedish welfare policy. The purpose of this article is to trace the trajectory of crime prevention and in particular the idea of cooperation as a crime policy solution. Dating back to the post-war decades, cooperation between authorities in an effort to tackle youth crime has also been in line with David Garland’s concept of penal welfarism. While Garland mainly focuses on penal institutions and penal law rather than prevention, cooperation in Sweden shares several characteristics with penal welfarism such as the optimistic belief in expert rule and individualized treatment. The professional expertise that colonized the field of criminal justice was an equally prominent feature of how schools would prevent crime. Against this background I also discuss whether or not the concept of the preventive turn is applicable to the trajectory of crime prevention in Sweden. My conclusion is that the development of crime prevention is best understood as a continuous process dating back to the post-war era’s focus on youth crime, as opposed to a break.